Medicinal plants used to treat snakebite in Central America: Review and assessment of scientific evidence. (6th March 2017) - Giovannini, Peter; Howes, Melanie-Jayne R.
Abstract: Ethnopharmacological relevance: Every year between 1.2 and 5.5 million people worldwide are victims of snakebites, with about 400, 000 left permanently injured. In Central America an estimated 5500 snakebite cases are reported by health centres, but this is likely to be an underestimate due to unreported cases in rural regions. The aim of this study is to review the medicinal plants used traditionally to treat snakebites in seven Central American countries: Belize, Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama. Materials and methods: A literature search was performed on published primary data on medicinal plants of Central America and those specifically pertaining to use against snakebites. Plant use reports for traditional snakebite remedies identified in primary sources were extracted and entered in a database, with data analysed in terms of the most frequent numbers of use reports. The scientific evidence that might support the local uses of the most frequently reported species was also examined. Results: A total of 260 independent plant use reports were recorded in the 34 sources included in this review, encompassing 208 species used to treat snakebite in Central America. Only nine species were reported in at least three studies: Cissampelos pareira L., Piper amalago L., Aristolochia trilobata L., Sansevieria hyacinthoides (L.) Druce, Strychnos panamensis Seem., Dorstenia contrajerva L., Scoparia dulcis L., Hamelia patens Jacq., and Simaba cedron Planch. Genera with the highest number of species used to treat snakebite were Piper, Aristolochia, Hamelia, Ipomoea, Passiflora and Peperomia . The extent of the scientific evidence available to understand any pharmacological basis for their use against snakebites varied between different plant species. Conclusion: At least 208 plant species are traditionally used to treat snakebite in Central America but there is a lack of clinical research to evaluate their efficacy and safety. Available pharmacological data suggest different plant species may target different symptoms of snakebites, such as pain or anxiety, although more studies are needed to further evaluate the scientific basis for their use. Graphical abstract: